2022
DOI: 10.1371/journal.pone.0267383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and validation of sunflower (Helianthus annuus L.) hybrids through SSR markers

Abstract: Genetic purity is a prerequisite for exploiting the potential of hybrids in cross-pollinated crops, such as sunflower. In this regard DNA-based study was conducted using 110 simple sequence repeat (SSR) markers to check the genetic purity of 23 parents and their 60 hybrids in sunflower. The polymorphism was shown in 92 markers with value 83.63%. The SSR markers ORS-453 and CO-306 showed the highest PIC values of 0.76 and 0.74, respectively. The primer ORS-453 amplified allele size of 310 base pairs (bp) for fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Another study that deals with the genetic aspect is the research work of H.G.M.D. Ahmed et al (2022), who examined the molecular characteristics of hybrid sunflower varieties and their authenticity. The results showed that 10 hybrids are authentic, i.e., their genetic characteristics match the description provided by the manufacturer.…”
Section: Table 15 Continuedmentioning
confidence: 99%
“…Another study that deals with the genetic aspect is the research work of H.G.M.D. Ahmed et al (2022), who examined the molecular characteristics of hybrid sunflower varieties and their authenticity. The results showed that 10 hybrids are authentic, i.e., their genetic characteristics match the description provided by the manufacturer.…”
Section: Table 15 Continuedmentioning
confidence: 99%
“…Another study that deals with the genetic aspect is the research work of H.G.M.D. Ahmed et al (2022), who examined the molecular characteristics of hybrid sunflower varieties and their authenticity. The results showed that 10 hybrids are authentic, i.e., their genetic characteristics match the description provided by the manufacturer.…”
Section: Table 15 Continuedmentioning
confidence: 99%